The first observed stellar occultations by the irregular satellite Phoebe (Saturn IX) and improved rotational period. Issue 1 (19th December 2019) - Gomes-Júnior, A R; Assafin, M; Braga-Ribas, F; Benedetti-Rossi, G; Morgado, B E; Camargo, J I B; Vieira-Martins, R; Desmars, J; Sicardy, B; Barry, T; Campbell-White, J; Fernández-Lajús, E; et al.
ABSTRACT: We report six stellar occultations by Phoebe (Saturn IX), an irregular satellite of Saturn, obtained between mid-2017 and mid-2019. The 2017 July 6 event was the first stellar occultation by an irregular satellite ever observed. The occultation chords were compared to a 3D shape model of the satellite obtained from Cassini observations. The rotation period available in the literature led to a sub-observer point at the moment of the observed occultations where the chords could not fit the 3D model. A procedure was developed to identify the correct sub-observer longitude. It allowed us to obtain the rotation period with improved precision compared to the currently known value from literature. We show that the difference between the observed and the predicted sub-observer longitude suggests two possible solutions for the rotation period. By comparing these values with recently observed rotational light curves and single-chord stellar occultations, we can identify the best solution for Phoebe's rotational period as 9.27365 ± 0.00002 h. From the stellar occultations, we also obtained six geocentric astrometric positions in the ICRS as realized by the Gaia DR2 with uncertainties at the 1-mas level.